2022
DOI: 10.1038/s41390-022-02063-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuromonitoring, neuroimaging, and neurodevelopmental follow-up practices in neonatal congenital heart disease: a European survey

Abstract: Background Brain injury and neurodevelopmental impairment remain a concern in children with complex congenital heart disease (CHD). A practice guideline on neuromonitoring, neuroimaging, and neurodevelopmental follow-up in CHD patients undergoing cardiopulmonary bypass surgery is lacking. The aim of this survey was to systematically evaluate the current practice in centers across Europe. Methods An online-based structured survey was sent to pediatric cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 42 publications
(43 reference statements)
0
19
0
Order By: Relevance
“…Surveys of neurodevelopmental follow‐up in Canada, Europe, and the UK highlighted the importance of having evidence‐based guidance to support standardization across geographical contexts, but which was also relevant to the local setting 15,16,43 . Guidelines produced in one setting may not always be appropriate for use in another, even with the same underpinning evidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surveys of neurodevelopmental follow‐up in Canada, Europe, and the UK highlighted the importance of having evidence‐based guidance to support standardization across geographical contexts, but which was also relevant to the local setting 15,16,43 . Guidelines produced in one setting may not always be appropriate for use in another, even with the same underpinning evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 21 studies examined the implementation of specific programmes or care pathways for neurodevelopmental follow-up care, [27][28][29][31][32][33][34][35][36][38][39][40]42,44,[47][48][49][50][51][52][53][54]56 and 12 studies reported on surveys or overviews of current clinical practices in neurodevelopmental follow-up. 9,[13][14][15][16]30,37,41,43,45,46,55 Implementation and evaluation of follow-up programmes or care pathways All studies were published after 2011, with most (15 out of 21) conducted since 2018. Fourteen of the studies reported on neurodevelopmental care pathways or programmes based in the USA, 27,[32][33][34][35][36][38][39][40]42,44,[46]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Although the need for standardized neurodevelopmental follow-up programs is recognized and specific recommendations have been issued, 45,46 the implementation is heterogeneous across different centers within and between countries. 47,48 Further, neurodevelopmental follow-up is often only available for those children with CHD considered at highest risk for neurodevelopmental impairments rather than for all children with CHD after open heart surgery. 47 Structured long-term evaluation programs for all high-risk children surviving neonatal critical illness are needed to ensure adequate follow-up care for these children as they grow.…”
Section: Discussionmentioning
confidence: 99%
“…Two centers (8%) reported no use of intraoperative neuromonitoring. 44 Given the relatively common use of NIRS, Loomba et al performed a systematic review with the objective of determining the correlation of NIRS oximetry and corresponding venous oxygen saturations using pooled analysis. A total of 13 studies, including 562 patients, showed a strong correlation (pooled correlation coefficient = 0.7, 95% CI 0.55-0.80) between cerebral NIRS oximetry values and superior vena cava or jugular venous oxygen saturations.…”
Section: Neuromonitoring For Pediatric Cardiac Surgerymentioning
confidence: 99%